India and bilateral investment treaties : refusal, acceptance, backlash - Ranjan, Prabhash (New Delhi : Oxford University Press, 2019)
Many countries have started contesting international investment treaties that allow foreign corporations to sue sovereign States for alleged treaty breaches at international arbitration fora. This contestation has taken the form of either countries terminating their investment treaties or walking out of the investor-State dispute settlement (ISDS) system. India has also jumped on the contestation bandwagon. As a consequence of being sued by more than 20 foreign investors, India terminated close to 60 investment treaties and adopted a new model bilateral investment treaty (BIT) purportedly to balance investment protection with the host State's right to regulate. This work studies critically India's approach towards BITs by tracing its origin, evolution, and the current state of play.
This edition also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 11, 2019).
Keywords: Investments, Foreign -- Law and legislation -- India; Investments, Foreign (International law); India -- Economic policy; India -- Foreign economic relations